EXPLORING THE ROLE OF VIDEO CONTENT MANAGEMENT IN TEACHER EDUCATION: STRATEGIES AND CHALLENGES - Laya A B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of Video Content Management (VCM) in teacher education has revolutionised instructional methodologies, offering dynamic and flexible learning experiences. This study examines the significance of VCM, the strategies employed in its adoption, and the challenges hindering its effective implementation in teacher education programs. Using qualitative research approach, the study incorporates content analysis along with interviews with 25 teacher educators to assess technological, pedagogical, and organisational barriers to VCM utilization. The findings highlight key challenges, including inadequate infrastructure, limited faculty training, financial constraints, and resistance to technological change. The study underscores the need for enhanced IT infrastructure, targeted faculty training, and clear policies for content management to optimize VCM’s benefits. By promoting accessibility, engagement, and innovative teaching strategies, institutions can leverage VCM to improve teacher education programs and foster an enriched digital learning environment. This research calls for strategic investments in digital education technologies to ensure effective and sustainable VCM implementation in teacher training.